Isolation and identification of dibenzofuran degrading marine bacteria from seawater of coast of Sarawak - Shah Hazizul, Bin Johari (Universiti Malaysia Sarawak (UNIMAS), 2011)
A dibenzofuran-utilizing marine bacterium, designated strain DBF01 was isolated from seawater in Miri, Sarawak. This strain grew aerobically with DBF as the principal sole carbon source and energy. In this study, Artificial seawater mineral salts medium (ONR7a) was used as the basal medium for isolating and culturing microorganisms. They produced a soluble opaque colored with ONR7a suspension culture and the isolate formed smooth, circular creamy-white, small-sized colonies on the surface of the ONR7a agar. Gram staining analysis showed that the isolate was a Gram-negative, short straight rod-shaped cell. Strain DBF01 required Na+ for growth and exhibited optimal growth at 3% NaCl. They were capable of degrading various different recalcitrant aromatic compounds including biphenyl, carbazole dibenzothiophene and fluorene. Strain DBF01 was obligately marine bacterium, aerobic, motile, oxidase and catalase positive. DNA extraction was carried out by PCI method and 16S rRNA gene sequence was amplified by universal primers (PA/PH), purified and sequenced. The 16S rRNA-based phylogenetics analysis has revealed that strain DBF01 belonged to γ-subclass of Proteobacteria. The species closest to strain DBF01 was Pseudomonas pachastrellae (99% similarity in 16S rRNA gene sequence). PTG4-14 is designated as the type strain (EU603457.1)